The #MeToo effect: what happens when we believe women - Gilmore, Leigh (Gender and culture, 2024)
Leigh Gilmore provides a new account of #MeToo that reveals how storytelling by survivors propelled the call for sexual justice beyond courts and high-profile cases. She reframes #MeToo as a breakthrough moment within a longer history of feminist thought and activism